An Exploratory Study of French University Students Pursuing L2 English: Career, Cyberlanguage, and Jargon/Slang - Bergami, Roberto; Aulino, Biagio (Common Ground Publishing, 2016)
This paper reports on an exploratory investigation of young (emerging adults) French university students who have been studying English as a second language (L2). The foci of this paper are twofold. The first is to establish the reasons for pursuing the study of L2 English. The second is to discover the use and influence of cyberlanguage on communications and whether including jargon/slang in the curriculum is desirable. The data reveal the majority of students pursue L2 English primarily for economic reasons, such as a better future employment opportunities and the chance to work in English speaking countries. The data showed a strong desire to have jargon/slang taught in the classroom, as respondents considered this an important aspect. This was not unexpected, particularly as the conclusion suggests the L2 syllabus needs rejuvenation to be more relevant and interesting to younger generations. Teaching jargon/slang should be included in the texts and classroom activities, as the command of such jargon/slang presupposes a good understanding of the base language (L2), especially when acronyms and substitutions are made common practice in cyberlanguage communications.
Keywords: Foreign Language Teaching, Learning English as Second Language for French, Virtual Social Networks